A Digital Calibration Method for a MEMS Accelerometer based on Harmonic Self-Test. (April 2020) - Chen, Dongliang; Liu, Xiaowei; Yin, Liang; QiangFu,
Abstract: This paper proposes a digital calibration method for electromechanical closed-loop MEMS accelerometer. The method based on a harmonic self-test mechanism, in which the MEMS structure is excited by an on-chip generated electrostatic force and the corresponding harmonic distortion could be captured and analysed as an indicator of structure mismatch. According the harmonic distortion level, the mismatch could be calibrated out by the electrical signal on-chip. The whole exciting and calibrating procedure is realized in digital domain. Thus, not only the area and power consumption are reduced, but also the flexibility and robustness of the procedure is enhanced.